Codeswitching in Facebook Statuses of College Students and their Grammatical Ability in Academic Writing - Riparip, Eduard (International Journal of Language and Literary Studies, 2024)
The study aimed to identify the relationship between the prevalent forms of codeswitching in the Facebook statuses of college students and their grammatical ability in their formal compositions. Descriptive research, using analysis, comparative and correlational methods, was employed in the study. The sets of data were gathered from 175 college students from the City of Manila, Philippines whose Facebook statuses were analyzed. The study revealed that intersentential codeswitching is the most prevalent codeswitching among college students followed by intra-word codeswitching, intrasentential codeswitching and tag-switching. Three grammatical error categories were evident in the subjects’ formal compositions namely, Error in Word Usage, Error in Mechanics, and Error in Sentence Construction. In general, there is no significant relationship between the prevalence of the subjects’ codeswitching in their Facebook statuses and the grammatical ability in their formal compositions. However, a slight correlation was noted in the case of intra-word codeswitching and word usage. This implies that intra-word codeswitching slightly influences the vocabulary skills of the students. Thus, language teachers are reminded of the importance of language use and functions in academic and professional writing. The teaching of vocabulary should be a primordial concern in teaching academic writing maximizing the use of text reading and professional writing. In addition, retooling of teaching strategies in grammar lessons should be highlighted in the course of the subject since grammatical errors are still prevalent in the students’ formal compositions.